Understanding Sigmund Freud's Psychoanalysis: From Libido to God - Yulius Sodah (Journal of Social Research, 2025)
Sigmund Freud is the most influential figure in the world of psychology, especially in the field of personality psychology. Freud's psychoanalysis consists of 2 basic theses that force people to rethink the intellectual, aesthetic, and moral beliefs that developed in their time. First, psychoanalysts believe that most of human life is influenced by the subconscious. This thesis overhauled the old view that mental activity is always conscious. The second thesis of psychoanalysis is that instinctive impulses, especially sexual impulses, play a very important role in human life and are the cause of various anxiety and mental disorders. However, instinct is not something that is always negative because instinct is a source of energy for human personal development. Freud's theories are based on these two basic theses including his theories of God and religion. This paper seeks to briefly explain the views of Sigmund Freud that influenced later psychological concepts as well as the world of philosophy and medicine.